2009
DOI: 10.1088/0004-637x/707/1/716
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Scattering Polarization of Substellar-Mass Objects: T Dwarfs

Abstract: While there have been multiple observational programs aimed at detecting linear polarization of optical radiation emitted by ultracool dwarfs, there has been comparatively less rigorous theoretical analysis of the problem. The general expectation has been that the atmospheres of those substellar-mass objects with condensate clouds would give rise to linear polarization due to scattering. Because of rotation-induced non-sphericity, there is expected to be incomplete cancellation of disk-integrated net polarizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 42 publications
2
67
1
Order By: Relevance
“…In addition, J1254−0122 (T2) is the coolest target in our sample. Sengupta & Marley (2009) theoretically studied the possible detection of linear polarization in the oblate atmospheres of cloudless T-type sources, which are even cooler than the L-types. Their calculations showed that polarization may arise only for λ ≤ 0.6 μm (a range where T-dwarfs are extremely faint), and the net disk integrated polarization may be neglible.…”
Section: Linear Polarization Versus Spectral Typementioning
confidence: 99%
“…In addition, J1254−0122 (T2) is the coolest target in our sample. Sengupta & Marley (2009) theoretically studied the possible detection of linear polarization in the oblate atmospheres of cloudless T-type sources, which are even cooler than the L-types. Their calculations showed that polarization may arise only for λ ≤ 0.6 μm (a range where T-dwarfs are extremely faint), and the net disk integrated polarization may be neglible.…”
Section: Linear Polarization Versus Spectral Typementioning
confidence: 99%
“…As in Sengupta & Marley (2010) we employ the gas and dust opacity, the temperature–pressure profile and the dust scattering asymmetry function averaged over each atmospheric pressure level derived by the atmosphere code in a multiple scattering polarization code that solves the radiative transfer equations in vector form to calculate the two Stokes parameters I and Q in a locally plane‐parallel medium (Sengupta & Marley 2009). For each model layer we fit a Henyey–Greenstein phase function to the particle scattering phase curve predicted by a Mie scattering calculation.…”
Section: Polarization Of Young Exoplanetsmentioning
confidence: 99%
“…Polarization of exoplanet radiation arises from scattering by either gas or dust in the atmosphere. Clear atmospheres lacking dust grains can be polarized, but only at blue optical wavelengths where gaseous Rayleigh scattering is important (Sengupta & Marley 2009). Even the hottest young exoplanets will not emit significantly in the blue.…”
Section: Introductionmentioning
confidence: 99%
“…We apply, for the first time [2][3][4], Chandrasekhar's formalism to estimate scattering polarization of the atmosphere of substellar mass objects. As the atmosphere of these objects is sufficiently cool, condensation of various molecular species takes place at the visible atmosphere and scattering by condensates yields detectable amount of polarization.…”
Section: Substellar Mass Objectsmentioning
confidence: 99%
“…These quantities are then used as inputs in a multiple scattering polarization code that solves the radiative transfer equations in vector form as given by Chandrasekhar to calculate the linear polarization in a locally plane-parallel medium. Finally, the polarization is integrated over the rotation-induced oblate disk of the object using a spherical harmonic expansion method [2].…”
Section: Atmospheric Modelmentioning
confidence: 99%